Observation of J/psi-->3gamma. - Adams, G; Anderson, M; Cummings, J; Danko, I; Hu, D; Moziak, B; Napolitano, J; He, Q; Insler, J; Muramatsu, H; Park, C; Thorndike, E; et al. (2008)
We report the first observation of the decay J/psi-->3gamma. The signal has a statistical significance of 6sigma and corresponds to a branching fraction of B(J/psi-->3gamma)=(1.2+/-0.3+/-0.2)x10;{-5}, in which the errors are statistical and systematic, respectively. The measurement uses psi(2S)-->pi;{+}pi;{-}J/psi events acquired with the CLEO-c detector operating at the CESR e;{+}e;{-} collider.